Neither magic bullet nor a mere tool: negotiating multiple logics of the checklist in healthcare quality improvement. Issue 4 (10th February 2019) - Kocman, David; Stöckelová, Tereza; Pearse, Rupert; Martin, Graham
Abstract: Over two decades, the checklist has risen to prominence in healthcare improvement. This paper contributes to the debate between its proponents and critics, making the case for an Science and Technology Studies‐informed understanding of the checklist that demonstrates the limitations of both the "checklist‐as‐panacea" and "checklist‐as‐socially‐determined" positions. Attending to the checklist as a socio‐material object endowed with affordances that call upon clinicians to act (Allen 2012, Hutchby 2001), the study revisits the efforts of a recent improvement initiative, the Enhanced Peri‐Operative Care for High‐risk patients trial. Rather than a singularised simple tool, this study discusses four different and relationally enacted logics of the checklist as a stop and check tool, a clinical prompt, an audit tool and a clinical record. Each logic is associated with specific temporality, beneficiaries, relationship with material forms, and interpellates (Law 2002) clinicians to initiate specific actions which can conflict. The paper seeks to make the case for intervention to improve such tools and consciously account for the consequences of their design and materiality and calls for supporting such settings and arrangements in which incoherences collected in tools can be locally negotiated.